If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (83 + -1x) + (5x + 11) = 109 Remove parenthesis around (83 + -1x) 83 + -1x + (5x + 11) = 109 Reorder the terms: 83 + -1x + (11 + 5x) = 109 Remove parenthesis around (11 + 5x) 83 + -1x + 11 + 5x = 109 Reorder the terms: 83 + 11 + -1x + 5x = 109 Combine like terms: 83 + 11 = 94 94 + -1x + 5x = 109 Combine like terms: -1x + 5x = 4x 94 + 4x = 109 Solving 94 + 4x = 109 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-94' to each side of the equation. 94 + -94 + 4x = 109 + -94 Combine like terms: 94 + -94 = 0 0 + 4x = 109 + -94 4x = 109 + -94 Combine like terms: 109 + -94 = 15 4x = 15 Divide each side by '4'. x = 3.75 Simplifying x = 3.75
| 1/y=y/9 | | F(x)=4x^2-17x-15 | | -2/5x=8 | | -3-6=13-10x | | 2x-27=-3x+93 | | 20x/5x^2+1 | | 2m-3=17-3m | | (17+4x)+(7+9x)=180 | | 1/x=1/7+4 | | 12+3x=0 | | 3/4x20-20 | | (X+2)/(x^2+25) | | 1/x=4 | | (18x-9)(4x+13)=180 | | y-8=2+5y | | 2(3x+1)=x+19 | | 64x^2=121 | | 485+x=445-x | | b/j+h=t | | 0.04(5t+2)=0.20(t-4)+0.88 | | (X+4)/(x^2-36) | | 3(2x+1)=5-(X-3) | | 7(4-z)/6=-z | | 2.4-5c=35.9 | | 6x+7=6x+15 | | 14-2x-5=2x+9 | | 8x+7=-8+6x+23 | | 2(6+9)-7= | | 4(2x-5)-3(2x-5)=29 | | 9x+27=45 | | 1.03Z+2.1=3.13 | | 5(x-9)+46=4(x+9) |